The role of marketing places in developing thermal spas in the North Region of Portugal - Antunes, Joaquim (2017)
Thermal spas have gained preponderance in developing sustainable tourism projects in several regions worldwide. However, thermal spas need to guide their development strategy in areas of intervention that should go beyond the traditional product, by basing the positioning on a product capable of satisfying different market segments. The aim of this paper is to study the thermal spa based on an integrated approach to the various stakeholders in order to create a strong brand that values and enhances the visibility and attractiveness of a region. It aims to focus that the effective use of marketing has become a simple tool to promote a spa resort and attract tourists, residents and organizations. Through an empirical study, based on the users of spa resorts on north region in Portugal, the factors that tourists consider more important when choosing a tourist destination were identified. These factors should be considered in future strategy decisions for sustainable development of thermal resorts.